Tecendo identidades profissionais: um estudo psicanalítico dos processos identificatórios na escolha de carreiras - Rosa, Mônica Pereira da (2025)
The objective of this thesis is to understand how identification factors act when choosing a profession and when restructuring a career. To this end, a theoretical review was carried out on the concept of identification in the work of Freud and his commentators. Fragments of some cases of professional and career guidance seen in a clinical situation were presented, and films cenários that add ress the theme of choosing a profession and its impact on the lives of professionals were also discussed. The research is justified by the need to better understand the internal and external processes that influence professional choice and satisfaction. This includes the analysis of psychological factors, such as identification models, desires, aptitudes and professional identity, as well as external factors, such as labor market conditions, social and family expectations and opportunities for professional development. The study addresses the process of professional choice from a psycho analytic perspective, with a nemphasis on identification processes that influence both young people seeking na initial career and adults in the process of professional restructuring. Based on clinical cases, film fragments and Freud’s fundamental concepts on identity, the research explored how family, sociocultural, economic, labor market and technological factors shape these choices. Profession plays a central role in the construction of identity and social belonging, functioning as a structuring element of subjectivity. Identifications, especially with parental figures, reveal coherence in the life trajectory, but can also generate conflicts when there is a discrepancy between individual desires and family expectations. The study concludes that choosing a profession is a process profoundly influenced by the identifications that the individual develops through out his or her life. These identifications, which emerge from significant relationships, social models and personal experiences, structure the subjectand play a decisive role in both the construction and crises of professional identity